العــقــل الإســـلامــي عند أركون : اسباب التخلف و رؤية للتجديد - من وجهة نظر محمد أركون - - حليلو, نبيل; مخنان, طارق (Sciences de l'Homme et de la Société; Vol. 18 (2016): SCIENCES DE L'HOMME ET DE LA SOCIÉTÉ, 2015)
في هذا المقال الذي نريد من خلاله ان نبين كيف استخدم محمداركون منهجية التفكيك على العقل العربي والإسلامي، وتوظيف الإسلاميات التطبيقية والتي يقصد بها أركون استخدام المناهج الغربية الحديثة في اعادة قراءة التراث الإسلامي، حتى يتسنى لنا الكشف عن اسباب توقف العقل الإسلامي واعادة تشغيله ليصل به الى اللحاق بركب التقدم الذي يعيشه نظيره العقل الغربي لأن العالم الإسلامي حسب اركون يعيش قطيعتين الأولى مع تراثه و الثانية مع الحداثة الغربية  وما أنتجته الحضارة المعاصرة In this article we want to show how Mohammed Arkoun uses the methodology of deconstruction on the Arab and the Islamic mind. In addition we want to show the employments of Applied Islamist, that are intended to Akron to use the modern western approaches to re-read the Islamic heritage, so that we can detect the causes of the Islamic mind stopped and re-run up to him to catch up the advances experienced counterpart western mind. Because the Islamic world according to Akron lives with two different determinism; first with his legacy & second with western modernity that produced by modern civilization.